La fotografía publicitaria como una herramienta de inbound marketing para un territorio. - Vizuete Salinas, Brigith Stephanie (2023)
Advertising photography as an inbound marketing tool for the Naranjito canton of the Guayas province is the title of this research. The importance of advertising photography represents an excellent opportunity for the tourist and economic growth of the canton. This study aimed to apply advertising photography as an inbound marketing tool to promote tourism in Naranjito canton of Guayas province. The methodology used a descriptive study of a cross-sectional type, a bibliographic modality, and a qualitative approach since a data collection instrument was executed for its respective analysis. The survey technique was used for the collection of data, whose sample had the collaboration of 216 national and foreign tourists. The main findings evidence that advertising photography is able to persuade and inform an effective and quality message that exceeds the desire to visit the tourist places of Cuenca; in addition, it allows the increase of economic resources and attracts the attention of travelers in a fast and efficient way without the use of lengthy texts that are difficult to understand.